2021
DOI: 10.1038/s41392-021-00805-y
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer cell-derived exosomal miR-1249-3p attenuates insulin resistance and inflammation in mouse models of type 2 diabetes

Abstract: Natural killer (NK) cells have been suggested to be associated with type 2 diabetes by regulating systemic inflammation. However, the mechanism by which NK cells regulate insulin sensitivity remains unknown. This study shows that NK-derived exosomes from lean mice attenuate obesity-induced insulin resistance and inflammation in mice of type 2 diabetes. Moreover, lean NK-derived exosomes enhance insulin sensitivity and relieve inflammation in adipocytes and hepatocytes. MiR-1249-3p, which is significantly upreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 48 publications
0
38
0
Order By: Relevance
“…MiR-1249 may inhibit the angiogenesis of human umbilical vein endothelial cells by targeting VEGF-A, 45 which is involved in endothelial cell proliferation and apoptosis. Furthermore, miR-1249-3p has attenuated insulin resistance and inflammation in a mouse model of type 2 diabetes, 46 is involved in the development of diabetes and its complications, 47–49 and can be used as a biomarker for diabetes and a potential target for the treatment of diabetes. Numerous studies have shown that miR-155-5p plays an important role in the progression of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-1249 may inhibit the angiogenesis of human umbilical vein endothelial cells by targeting VEGF-A, 45 which is involved in endothelial cell proliferation and apoptosis. Furthermore, miR-1249-3p has attenuated insulin resistance and inflammation in a mouse model of type 2 diabetes, 46 is involved in the development of diabetes and its complications, 47–49 and can be used as a biomarker for diabetes and a potential target for the treatment of diabetes. Numerous studies have shown that miR-155-5p plays an important role in the progression of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it might be that metabolism-regulating miRNAs play a vital role in the dynamics of metabolic homeostasis. 256 …”
Section: The Insulin Signaling and Irmentioning
confidence: 99%
“…The miR-17-5p-Mfn1/2-NF-ΚB pathway has anti-inflammatory and anti-apoptotic effects in GDM [ 82 ]. miR-1249–3p has reduced IR and inflammation in a mouse model of T2DM [ 83 ]. miRNA-26a promotes regulatory T cells to suppress T1DM [ 84 ].…”
Section: The Importance Of Exosomes In Diabetes Researchmentioning
confidence: 99%